The recognition of gaming disorder in China: a case series of 223 patients - Shao, Tianli (PeerJ, 2021)
BACKGROUND: Internet gaming disorder (IGD) was listed in the appendix of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) as a condition requiring further study in 2013, and gaming disorder (GD) was considered a mental disorder and listed in the 11th International Classification of Diseases Manual (ICD-11) in 2018. The study aims to obtain preliminary knowledge of the recognition of GD in China. METHODS: A total of 223 Chinese patients who met both the ICD-11 and DSM-5 criteria for GD participated in the study, and a self-administered questionnaire was used to collect demographic information, gaming use characteristics, and previous diagnoses. RESULTS: The average age of patients with GD was 20.5 years, and 71.3% were male. Most patients were diagnosed with emotion-related disorders at their first psychiatric visit: mood disorders (59.2%), bipolar affective disorder (18.4%), depressive episode (12.6%), and anxiety disorder (4.9%). Among the adolescent patients with a first diagnosis of mood disorders, 71.2% and 33.3% were diagnosed with bipolar affective disorder and personality disorders, respectively, at subsequent visits. Overall, after the first visit, the most common diagnosis was bipolar affective disorder (61.0%), followed by personality disorders (34.1%), mood disorders (17.0%), depressive episode (17.0%), and other disorders. Only three patients had Internet overuse. CONCLUSION: The identification rate of GD is extremely low in routine psychiatric clinical practice in China. Most patients with GD were previously misdiagnosed with emotion-related disorders. Psychiatrists should be trained to improve their ability to recognize and manage GD.